Pengaruh Metode Pembelajaran STAD Berbantuan Media Manipulatif Math Adventure terhadap Kemampuan Kognitif pada Pelajaran Matematika Kelas 1 MI - Cahyati, Linda; Agustin, Nurhaningtyas (Paedagogie, 2026)
This research is motivated by the low cognitive ability of 1st-grade elementary students (MI) in mathematics, particularly in addition and subtraction materials. The main problems include conventional and monotonous teaching methods, low student interest, and students' difficulties in distinguishing between arithmetic operations. The purpose of this study is to determine the significant influence of the Student Teams Achievement Division (STAD) method supported by Math Adventure manipulative media on students' cognitive abilities. The methodology used is a quantitative approach with a pre-experimental research design. The population and sample of the study consist of all 22 students in the 1st grade of MI Islamiyah Pakel Tuban for the 2025/2026 academic year. Data collection instruments include observation sheets, documentation, and cognitive ability tests (pre-test and post-test). Data analysis techniques utilize validity, reliability, normality, and homogeneity tests, as well as hypothesis testing using the SPSS program. Data collection was carried out through essay tests given in the form of a pre-test and post-test, which were then analyzed using descriptive and inferential statistics. The research results indicate that the average post-test score of the experimental group is higher than that of the control group. The paired sample t-test shows a significant difference between the pre-test and post-test scores in both groups, while the independent sample t-test shows a significant difference between the students' critical thinking skills in the experimental and control groups. Based on the data analysis, it is concluded that there is a significant influence of the combination of the method and media on the improvement of students' cognitive abilities in mathematics learning.